Respons dan Adaptasi Pesantren Daar El-Qolam Tangerang terhadap Pandemi Covid 19 - Nur Alia; Nursalamah Siagian (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Daar el-Qolam Islamic Boarding School is one of the relatively large Islamic boarding schools with more than a thousand students, and located in the red zone or at high risk of spreading Covid-19. This paper examines how the Daar el-Qolam responds to various government policies related to the Covid-19 pandemic, as well as adaptation strategies undertaken in the face of the pandemic. The research was conducted in June 2020 using a qualitative approach. The results show that Daar el-Qolam conforms in responding to various government policies related to the pandemic. When the government issued a new policy, Daar el-Qolam tried to follow the policy even though he had to change the existing policy or system. One of them is by repatriating students and stopping all activities at the boarding school. Thus, Daar el-Qolam's conformity can be seen from its efforts to always be in harmony and in accordance with group norms, which in this case is government policy. Meanwhile, the adaptations made by Daar el-Qolam are autoplastic and alloplastic. Autoplastic is carried out when Daar el-Qolam changes various internal policies to adapt to pandemic conditions, such as sending students home prematurely, conducting online learning, and providing facilities that comply with health protocols. Meanwhile, alloplastic is carried out when Daar el-Qolam changes the environment to suit the desired conditions, such as re-activating Islamic boarding school activities but with various changes in the learning process, santri lifestyle, and social and religious behaviour.